Self-Encapsulation of Biomacromolecule Drugs in Porous Microscaffolds with Aqueous Two-Phase Systems - Jian Kang; Yunpeng Cai; Ziwei Wu; Siyi Wang; Wei-En Yuan (MDPI AG, 2021)
At present, the most commonly used methods of microencapsulation of protein drugs such as spray drying, multiple emulsification, and phase separation, can easily cause the problem of protein instability, which leads to low bioavailability and uncontrolled release of protein drugs. Herein, a novel method to encapsulate protein drugs into porous microscaffolds effectively and stably was described. Ammonium hydrogen carbonate (NH4HCO3) was employed to prepare porous microscaffolds. α-Amylase was encapsulated into the porous microscaffolds without denaturing conditions by an aqueous two-phase system (PEG/Sulfate). The pores were closed by heating above the glass transition temperature to achieve a sustained release of microscaffolds. The pore-closed microscaffolds were characterized and released in vitro. The integrity and activity of protein drugs were investigated to verify that this method was friendly to protein drugs. Results showed that the pores were successfully closed and a high loading amount of 9.67 ± 6.28% (w/w) was achieved. The pore-closed microscaffolds released more than two weeks without initial burst, and a high relative activity (92% compared with native one) of protein demonstrated the feasibility of this method for protein drug encapsulation and delivery.